Changes in self-reported cannabis use during the COVID-19 pandemic: a scoping review - Kamna Mehra; Jennifer Rup; Jessica L. Wiese; Tara Marie Watson; Sarah Bonato; Sergio Rueda (BMC, 2023)
Abstract Background The COVID-19 pandemic is affecting mental health and substance use (MHSU) issues worldwide. The purpose of this study was to characterize the literature on changes in cannabis use during the pandemic and the factors associated with such changes. Methods We conducted a scoping review by searching peer-reviewed databases and grey literature from January 2020 to May 2022 using the Arksey and O'Malley Framework. Two independent reviewers screened a total of 4235 documents. We extracted data from 129 documents onto a data extraction form and collated results using content analytical techniques. Results Nearly half (48%) of the studies reported an increase/initiation of cannabis use, while 36% studies reported no change, and 16% reported a decrease/cessation of cannabis use during the pandemic. Factors associated with increased cannabis use included socio-demographic factors (e.g., younger age), health related factors (e.g., increased symptom burden), MHSU factors (e.g., anxiety, depression), pandemic-specific reactions (e.g., stress, boredom, social isolation), cannabis-related factors (e.g., dependence), and policy-related factors (e.g., legalization of medical/recreational cannabis). Conclusion Public health emergencies like the COVID-19 pandemic have the potential to significantly impact cannabis use. The pandemic has placed urgency on improving coping mechanisms and supports that help populations adapt to major and sudden life changes. To better prepare health care systems for future pandemics, wide-reaching education on how pandemic-related change impacts cannabis use is needed.